Private farmers' compensation and viability of protected areas: The case of Nairobi National Park and Kitengela dispersal corridor - Rodríguez, L.C.; Henson, D.; Herrero, Mario; Nkedianye, D.; Reid, Robin S. (Informa UK Limited, 2012)
Nairobi National Park (NNP) is unable to incorporate the spatial and temporal dynamics of many migratory mammals that rely on the area as a dry season refuge because of its small size. During the wet season, wildlife must be able to migrate to the south into the Kitengela dispersal area. This area is privately owned and rapidly undergoing land-use change, which affects the structure and function of the dispersal corridors, jeopardising the ecological sustainability of the park. Private landholders in Kitengela incur most of the costs of keeping the dispersal areas open, but do not receive any compensation or revenue from benefits derived from tourism in the park. Here we present an analysis of the willingness-to-pay (WTP) for Nairobi and Kitengela residents for a new land management scheme in the dispersal area, in which local pastoralists leave their land open to wildlife and, by not engaging in fencing, land subdivision or poaching activities, receive monetary compensation for the incremental costs derived from use of their properties as a wildlife dispersal area. The results suggest that the aggregated financial support of urban residents might represent around $1.2 million per year for 5 years. This amount exceeds the economic losses caused by wildlife in the dispersal area, and different financial schemes of fund investment and the prioritisation of conservation regions could be implemented to ensure payments and keep the dispersal corridors open in perpetuity.